Day 3 Thu, March 24, 2016 2016
DOI: 10.4043/26695-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Study of a Novel Inter Pipe Coating Material for Paraffin Wax Deposition Control and Comparison of the Results with Current Mitigation Technique in Oil and Gas Industry

Abstract: Hydrocarbon liquid consists of a range of components with different physico-chemistry characterization. Sometimes there are heavy component with crude oil such as asphaltene, naphthenic and paraffinic wax components and etc. Deposition of wax in both onshore and offshore pipelines presents a costly problem in the production and transportation of oil. There are several parameters contributing to wax deposition in multiphase crude oil flow, e.g. pressure drop, flow rate, pipe internal body surface roughness, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…When the flow rate exceeded a critical value, the paraffin deposition rate would decrease rapidly. The experimental results proved the importance of shear stripping in the paraffin deposition in petroleum pipelines (Rashidi et al 2016).…”
Section: Shear Stripping and Agingmentioning
confidence: 73%
See 2 more Smart Citations
“…When the flow rate exceeded a critical value, the paraffin deposition rate would decrease rapidly. The experimental results proved the importance of shear stripping in the paraffin deposition in petroleum pipelines (Rashidi et al 2016).…”
Section: Shear Stripping and Agingmentioning
confidence: 73%
“…This is due to the fact that the methyl groups on the surface of the PP reduce the surface density of the hydrogen atoms and hinder the interaction between the alkyl groups and the surface in crude oil. Rashidi et al (2016) studied the effect of the surface roughness of the coating in a submarine pipeline on the deposition of paraffin in Malaysia with polyvinyl chloride (PVC) and ethylenetetrafluoroethylene (ETFE), and the influence of crude oil cooling rate and flow velocity of different coatings of paraffin deposition (see Fig. 2).…”
Section: Low Surface Energy Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn controls the work of adhesion of paraffin on the surface. Rashidi et al [176] recently showed approximately 86% reduction in grams of paraffin wax deposition from Malaysian (Tapis) crude oil on ethylene-tetrafluoroethylene versus steel and PVC. Finally, substrates coated with DLC (surface energy of approx.…”
Section: Paraffins and Wax Depositionmentioning
confidence: 99%
“…Therefore, if there is no any prevention or management strategy in place, the precipitated solid could lead to the formation of wax deposit on the surface of the facilities, which could consequently decrease the oil recovery, and increase pumping cost. In the worst-case, the facilities could completely be blocked, causing significantly economic losses that may even lead to abandoning the wells (Adeyemi and Sulaimon, 2012;Matzain et al, 2002;Rashidi et al, 2016;Rittirong et al, 2015;Sanjay et al, 1995;Singh et al, 2000). This particularly occur in a low temperature environment such as the offshore production (Halstensen et al, 2013;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%